Analisis Campur Kode dalam Tayangan Skakmat : Anies Baswedan pada Youtube Pandji Pragiwaksono - Alfiarum Cahyani (PUSTAKA: Jurnal Bahasa dan Pendidikan, 2024)
The research investigates the phenomenon of code mixing in the film "Skakmat: Anies Baswedan" featured on Pandji Pragiwaksono's YouTube channel. The research aims to identify various types of code blends, driving elements, and their effects on audience understanding. This research uses a qualitative approach. According to the results of the analysis carried out on 15 matching tables consisting of 18 data, the dominance of outer code mixing and mixing of mixed code (hybrid code mixing). In such conversations, the interviewer is more likely to use a mix of codes than his counterpart. This phenomenon reflects the background of speakers as public figures with higher education, as well as the dynamics of increasingly diverse and global societies. This study improves our understanding of the use of language in social media and its relationship with sociolinguistics. Then it would be natural for the inner code mixing code to be found less because the speakers use the Indonesian language.